Standardization of tuna (Parathunnus Mebachi) ham production at pilot scale - Cabi, Evelyn C. (1994., 1994)
The study was conducted in order to standardize the production of Tuna Ham at pilot scale. Preliminary studies on Tuna Ham p[roduction based on BFAR formulation and process were made prior to the three phases of the study. Phase I involved the standardization of the formulation and process of Tuna Ham at laboratory scale. The time of brewing at 90-100 C was determine uding three different times: 60 inutes, 90 minutes and 120 minutes. The samples were evaluated for their sensory characteristics and the best product was that brewed for 90 minutes. Phase II involved the translation of Tuna Ham production from laboratory to pilot scale. The amount of the raw materials were increwased to ten times that used in the laboratory scale. This phase also included the examination of of the sensory attributes and the chemical and microbial characteristics of the product. Phase III involved the consumer acceptability test and ptoduct costing of Tuna Ham. The results of the sensory evaluation obtained from thge ffirst to the third phase were analyzed using statistical methods like ANOVA (Analysis of Variance) and DMRT (Duncan's Multiple Ranmge Test).
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fish -- Processing; Tuna